Ketaatan Imam Diosesan dalam Malam Gelap Iman: Refleksi Mistik Menghadapi Krisis Spiritual Pribadi - Laritmas, Stanislaus (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2026)
This research explores the spiritual dynamics of diocesan priests in facing the phase of the dark night of the soul, a condition of spiritual emptiness that often triggers a vocational crisis. The objective of the study is to analyze how obedience to the Bishop and the local Church serves as an instrument of mystical purification and a pillar of vocational stability. Utilizing a qualitative method through a literature review and phenomenological analysis, this study examines texts of mystical theology, canon law, and contemporary literature. The research findings indicate that obedience during times of darkness is not merely a matter of juridical compliance, but rather an act of pure faith (naked faith) that purifies the soul from egoistic attachments. Obedience functions as a theological anchor that enables the priest to remain faithful to objective ministry despite the loss of subjective consolation. The implications of this research emphasize the importance of adequate spiritual direction and the strengthening of presbyteral fraternity within ongoing formation to maintain the priest's spiritual resilience. Ultimately, obedience tested in the dark night transforms the priest into a more humble and authentic alter Christus.